Prof. Chrysis Sofianos — Deep Plane Facelift — Johannesburg - Sofianos, Chrysis (DEEPPLANE™, 2026)
Surgeon profile record for Prof. Chrysis Sofianos, practicing in Johannesburg, South Africa. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003264; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; south africa; johannesburg